Gender representation of characters in Palanca Award winning short stories for children 1989-2004 - Dery, Zipporah M.; Punzalan, Ricardo L. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Children's literature is very significant in one's development. Children could learn how to perceive themselves as well as the objects around them from the books they read. They could also project themselves in the character involved in the material and relate the persona's gender and pursuit or interest with reference to them and their own gender. Since children's literature could influence one's understanding of the world as well as gender development, it is significant to observe how characters in such materials are portrayed according to their gender and find out if equal gender representation is present.
The population used in this study are the 108 winners of Carlos Palanca Memorial Awards for Literature under the category Short Stories for Children. The variables identified are (1) frequency of mention of male and female characters in the story, (2) frequency of involvement of male and female characters in the story, (3) frequency of mention of male and female protagonists in the story and (4) the occupations male and female characters assume. The above-mentioned variables are used in analyzing Filipino and English short stories for children as well as first place winners in both language divisions.
After content analyzing the stories, the researcher found out that there are more male characters than female characters mentioned in the titles. Males outnumber females in the frequency of involvement of characters in the story. There is a larger number and wider variety of occupations assumed by male characters than female characters. Domestic or housekeeping pursuits such as laundrywoman, yaya and weaver are kept by females as well as teaching occupation like teacher and tutor. On the other hand, pursuits as mayor and principal, which are administrative occupations are assumed by males. They also often portray occupations that are less related to homemaking and that require physical strength and are done outside the house like warrior, hunter and fisherman. The incidence of male protagonists scored higher than female protagonists.
At some aspects, there are stories that tried to evoke impartiality among genders by asserting that females are capable of endeavors males perform and by breaking the traditional representation of characters using stereotyped roles and occupations.
But the stereotyped depictions of genders in terms of the occupations they assume are strong and apparent and the higher frequency of male character involvement than female character confirm that males still receive primary over females. Thus, the research concludes that gender bias is present in such materials.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Carlos Palanca Memorial Awards in Literature -- Literary Collections; Gender identity in literature; Children's literature -- Stories, plots, etc